IMPLEMENTASI MODEL PENGUKURAN BULLWHIP EFFECT MENGGUNAKAN MODEL MA(1) - Tita Talitha (TECHNO SCIENCE, 2010)
In supply chain management, one of the most critical problems which require a lot ofeffort with is how to quantify and alleviate the impact of bullwhip effect. Fault information canmake distortion of information which one of the consequence is variance of demand on supplychain channel. In fact, variability disposed moving upstream that is bullwhip effect phenomenon.In this research, a measure of bullwhip effect will be developed through moving average model,MA(1). From the resulting bullwhip measurement model can be implemented because the valueof r >-0.5.